Study of fuel cell co-generation systems applied to a dairy industry - Leal, E. M.; Silveira, J. L. (Elsevier B.V., 2002)
This paper presents a methodology for the study of a molten carbonate fuel cell co-generation system. This system is applied to a dairy industry of medium size that typically demands 2100 kW of electricity, 8500 kg/h of saturated steam (P = 1.08 MPa) and 2725 kW of cold water production. Depending on the associated recuperation equipment, the co-generation system permits the recovery of waste heat, which can be used for the production of steam, hot and cold water, hot and cold air. In this study, a comparison is made between two configurations of fuel cell co-generation systems (FCCS). The plant performance has been evaluated on the basis of fuel utilisation efficiency and each system component evaluated on the basis of second law efficiency. The energy analysis presented shows a fuel utilisation efficiency of about 87% and exergy analysis shows that the irreversibilities in the combustion chamber of the plant are significant. Further, the payback period estimated for the fuel cell investment between US$ 1000 and US$ 1500/k-W is about 3 and 6 years, respectively. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: fuel cell; co-generation; energy analysis; exergy analysis; economic analysis